PENGGUNAAN PENDEKATAN POSITIVE BEHAVIOR SUPPORT UNTUK MENGURANGI PERILAKU SELF-INJURY MEMBENTURKAN KEPALA PADA ANAK AUTIS DI SLB - LATIFIANA, TINA (Jurnal Pendidikan Khusus, 2016)
Abstract The autism children had problem in the domain of social interaction, communication (language and speech), emotion-behavior, playing pattern, sensory impairment, and low development or abnormal. One of the emotion-behavior problems was self-injury behavior. Self-injury was all activities which were done by someone and it could lead danger or injury to oneself. Self-injury behavior happened to the children selves was in the form of head banging activity through either the wall or other surfaces which disturbed so much in the learning process so it required an exact handling. One of the alternative handlings in reducing self-injury behavior of head banging was by Positive Behavior Support involving six systematic steps as the following: forming behavior support team, planning focused to the children, functional behavior assessment, making hypothesis A-B-C, planning of developing behavior support and monitoring the result. This research used experiment kind with Single Subject Research (SSR) design A-B, with the subject one autism child initialed ARA in SLB Cita Hati Bunda Sidoarjo. The technique of data collection used was direct observation using observation sheet of baseline phase (A) and intervention phase (B) and observation sheet A-B-C (Antecedent-Behavior-Consequences). The technique of data analysis used was visual analysis in condition and among condition. Based on the research result, it could be concluded that self-injury behavior of head banging to autism children could be reduced with Positive Behavior Support approach. This was indicated from the observation result of behavior frequency to baseline phase (A) beginning from 0,1,2 it reduced to intervention phase (B) beginning from 3,2,1 with trend tendency from up (baseline phase) to down (intervention phase) and stability tendency from variable to stable.     Keywords: Positive Behavior Support, self-injury behavior of head banging